تشكل الشقوق في الجدران البيتونية المسلحة المرتبطة بالأساس – المشكلة والحلول - طريفي, زكائي (Latakia University Journal -Engineering Sciences Series, 2014)
تعتبر الشقوق من العيوب الهامة في العناصر البيتونية، لوحظ بعد صب الجدران البيتونية المسلحة المرتبطة بالأساس أنه بعد فترة زمنية قصيرة من تصلب البيتون، ودون أي تحميل للجدران تتشكل شقوق طولية نافذة وعادة تكون بمسافات منتظمة على طول الجدار مما استرعى انتباهنا لهذه الظاهرة، وقد حصلت في عدة مشاريع هندسية . قمنا من خلال هذا البحث بوصف الحالة، وشرحها، وتحليلها، ودراسة أسباب تشكلها.وذلك من خلال دراسة ميدانية لثلاثة مشاريع هندسية منفذة في اللاذقية وهي عبارة عن حوض ترسيب، ومبنى فندق سياحي ومول تجاري، حيث تراوح عرض الشقوق مابين 1.25 mm وحتى 3 mm ، واختلف ارتفاعها في كل حالة مدروسة. تم في ختام البحث وضع الحلول العملية لتجنب هذه الظاهرة ومنها اعتماد فواصل طولية للجدران البيتونية المسلحة بتباعد حوالي ثلاثين مرة سماكة الجدار وذلك لتجنب الشقوق الناجمة عن التقلص والإجهادات الحرارية، حيث يكون عمق الفاصل حوالي 20 mm وعرضه مابين 15 mm حتى 20 mm وينفذ من جهتي الجدار الداخلية والخارجية. بعد تصلب البيتون وفك القالب الخشبي تملأ هذه الفواصل بمواد مالئة مرنة . Cracks are considered important defects in concrete elements. It was noticed after constructing the reinforced concrete walls related to the Foundation, that after a short time after the hardening of concrete and without any overloading on the wall, there have been vertical cracks of regular distances along each wall we noticed this phenomenon it had happened in many construction projects. We have described the situation and we have also explained and analyzed it by examining its reasons by a thorough study of three projects carried out in lattakia including scale decanter, building of a tourist hotel and a trade centre. Which crack width ranging from 1.25 mm to 3 mm, the height differed in each case studied. Ultimately, we have found the practical solutions to avoid this phenomenon, including adoption of longitudinal joints for reinforced concrete walls, spacing is about thirty times the wall thickness, in order to avoid cracks caused by shrinkage and thermal stress, where the depth of joint about 20 mm, and the width ranging between 15 mm to 20 mm, implemented on both sides of the wall internal and external. After hardening of concrete and lifting the wooden template fill the joints with filler flexible materials.